Social Media Protest and Resistance: Case of Indonesia Job Creation Bill Policy and Myanmar Government Coup Issue - Misran, Misran; Sutan, Arissy Jorgi; Efendi, David (Jurnal Komunikasi, 2023)
This study aims to analyze social media protests and resistance to the Job Creation Bill policy and the problem of a government coup. The protests and resistance in Indonesia were in the form of the Job Creation Bill in October 2020. Meanwhile, the protests and resistance in Myanmar in February 2021 were related to the Military Coup. The objects analyzed are related to the use of social media platforms to discuss the Rejection of the Omnibus law Bill on Job Creation in Indonesia and the Military's Rejection of the Government Coup in Myanmar. The method used in this research is a qualitative method with an analytical approach to Qualitative Data Analysis Software (Q-DAS). The data source in this study uses secondary data by taking data from social media, Twitter. The findings in this study include the narratives and themes and the reactions of Myanmar and Indonesia using social media to convey the history of resistance. Second, the relationship between the hashtags of protest and resistance in Myanmar is more substantial than in Indonesia. This shows that the relationship between Hastags and Myanmar is more potent than in Indonesia. Third, the distinctive narratives and use of hashtags displayed in Indonesia and Myanmar are connected with different hashtags with the same goal of protest and resistance in each country. In both cases, social media relationships are prominently displayed. Research Limitation is data limited on social media data.